Chronic total occlusion percutaneous coronary intervention in octogenarians and nonagenarians. Issue 6 (16th February 2021) - Vemmou, Evangelia; Alaswad, Khaldoon; Patel, Mitul; Mahmud, Ehtisham; Choi, James W.; Jaffer, Farouc A.; Doing, Anthony H.; Dattilo, Phil; Karmpaliotis, Dimitri; Krestyaninov, Oleg; Khelimskii, Dmitrii; Nikolakopoulos, Ilias; et al.
Abstract: Objective: The outcomes of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) in octogenarians and nonagenarians have received limited study. Methods: We compared in‐hospital outcomes of CTO PCI between patients ≥80 vs. <80‐years‐old in 6233 CTO PCIs performed between 2012 and 2020 at 33 U.S. and international centers. Results: There were 415 octogenarians and nonagenarians in our study (7% of the total population). Compared with younger patients, octo‐ and nonagenarians were less likely to be men (73% vs. 83.2%, p < 0.0001) and more likely to have atrial fibrillation (27% vs. 12%, p < 0.0001) and prior coronary artery bypass graft surgery (CABG) (43% vs. 29%, p < 0.0001). They were more likely to have CTOs with moderate/severe calcification (71% vs. 46%, p < 0.0001), but had similar mean J‐CTO scores (2.5 ± 1.3 vs. 2.4 ± 1.3, p = 0.08). They had lower technical and procedural success (82.2% vs. 86.3%, p = 0.0201; 80.3% vs. 84.8%, p = 0.016, respectively) and higher incidence of in‐hospital major adverse cardiovascular events (3.4% vs. 1.8%, p = 0.021). On multivariable analysis PCI in octo‐ and nonagenarians was not independently associated with technical and procedural success or with in‐hospital MACE. Conclusion: CTO PCI is feasible in octo‐ and nonagenarians, although success rates are lower, and the risk of complications is higher compared with younger patients, likely related to more comorbidities and higher coronary lesion complexity.